Debt‐relief programs and money left on the table: Evidence from Canada's response to COVID‐19. (17th February 2022) - Allen, Jason; Clark, Robert; Li, Shaoteng; Vincent, Nicolas
Abstract: This paper analyzes the effectiveness of debt‐relief programs targeting short‐run household liquidity constraints implemented in Canada in response to the COVID‐19 pandemic. These programs allowed individuals to push off mortgage and credit card payments and cut in half interest rates on credit card debt. Using credit bureau data, we document that, despite potential savings above $4 billion, enrolment was limited: 24% for mortgages and 7% for credit cards. By exploiting the richness of our data set, we provide evidence that close to 80% of individuals were unaware of the credit card relief program while others faced important fixed non‐monetary costs preventing uptake. Résumé: Nous analysons l'efficacité de mesures d'allégement financier aux emprunteurs mises en place par les institutions financières canadiennes durant la pandémie de COVID‐19. Ces mesures offraient aux ménages l'occasion de repousser leurs paiements hypothècaires ou de cartes de crédit. À l'aide de données sur les comptes de crédit individuels, nous documentons que malgré le fait que ces programmes offraient des économies potentielles de plus de 4 milliards de dollars, les taux de recours ont été faibles: 24 % pour les prêts hypothécaires et 7 % pour les cartes de crédit. Nous montrons également que près de 80 % des individus n'étaient pas au courant du programme d'allègement pour les cartes de crédit alors que d'autres n'ont pas déposé de demande en raison de la présence de coûts non monétaires fixes.